A versatile set of Lifeact-RFP expression plasmids for live-cell imaging of F-actin in filamentous fungi - Alexander Lichius; Nick D. Read (Fungal Genetics Reports, 2010)
Here we report the construction and application of a range of expression plasmids designed to facilitate live-cell imaging of F-actin dynamics in filamentous fungi simultaneously with other, preferably GFP-tagged fusion proteins. Pros and cons of the use of three different red fluorescent proteins (RFPs), two different promoters and three different selection markers are addressed.